Manajemen Kurikulum Pendidikan Karakter Berbasis Nilai-Nilai Keagamaan - Ubaidillah, Aan Eko Khusni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Education requires good management including Islamic education. The main aspect of the success of national education is the curriculum. Therefore, good management (management / regulation) of a curriculum is a necessity in achieving educational goals. Curriculum management is a curriculum management system that is cooperative, comprehensive, systemic, and systematic in order to achieve the goals of the curriculum. Character education should be carried out in a planned and measured stage and have a strong foundation, especially religious-based values.